Pig cognitive bias affects the conversion of muscle into meat by antioxidant and autophagy mechanisms. (18th April 2017) - Potes, Y.; Oliván, M.; Rubio-González, A.; de Luxán-Delgado, B.; Díaz, F.; Sierra, V.; Arroyo, L.; Peña, R.; Bassols, A.; González, J.; Carreras, R.; Velarde, A.; et al.
Abstract : Slaughter is a crucial step in the meat production chain that could induce psychological stress on each animal, resulting in a physiological response that can differ among individuals. The aim of this study was to investigate the relationship between an animal's emotional state, the subsequent psychological stress at slaughter and the cellular damage as an effect. In all, 36 entire male pigs were reared at an experimental farm and a cognitive bias test was used to classify them into positive bias (PB) or negative bias (NB) groups depending on their decision-making capabilities. Half of the animals, slaughtered in the same batch, were used for a complete study of biomarkers of stress, including brain neurotransmitters and some muscle biomarkers of oxidative stress. After slaughter, specific brain areas were excised and the levels of catecholamines (noradrenaline (NA) and dopamine (DA)) and indoleamines (5-hydroxyindoleacetic acid and serotonin (5HT)) were analyzed. In addition, muscle proteasome activity (20S), antioxidant defence (total antioxidant activity (TAA)), oxidative damage (lipid peroxidation (LPO)) and autophagy biomarkers (Beclin-1, microtubule-associated protein I light chain 3 (LC3-I) and LC3-II) were monitored during early postmortem maturation (0 to 24 h). Compared with PB animals, NB pigs were more susceptible to stress, showing higher 5HT levels ( P <0.01) in the hippocampus and lower DA ( P <0.001) in the pre-frontal cortex. Furthermore, NB pigs had more intense proteolytic processes and triggered primary muscle cell survival mechanisms immediately after slaughter (0 h postmortem ), thus showing higher TAA ( P <0.001) and earlier proteasome activity ( P <0.001) and autophagy (Beclin-1, P <0.05; LC3-II/LC3-I, P <0.001) than PB pigs, in order to counteract the induced increase in oxidative stress, that was significantly higher in the muscle of NB pigs at 0 h postmortem (LPO, P <0.001). Our study is the first to demonstrate that pig's cognitive bias influences the animal's susceptibility to stress and has important effects on the postmortem muscle metabolism, particularly on the cell antioxidant defences and the autophagy onset. These results expand the current knowledge regarding biomarkers of animal welfare and highlight the potential use of biomarkers of the proteasome, the autophagy (Beclin-1, LC3-II/LC3-I ratio) and the muscle antioxidant defence (TAA, LPO) for detection of peri-slaughter stress.